Ectoparasites in rats and shrews data related to leptospirosis in West Jakarta - Susanna, Dewi; Nova, Rusyda Ihwani Tantia; Laura, Rozek (Zenodo, 2021)
This study aimed to determine the presence and species of the rats and shrews that can potentially cause leptospirosis in West Jakarta and the species of ectoparasites found in them. Methods: The research was a descriptive study employing a cross-sectional approach. The study population was all species of rats and shrews in the region and the sample collection technique used was purposive sampling. The traps were installed in the homes of respondents who had suffered from leptospirosis and their closest neighbors with a total of 521 traps. Leptospirosis data based on secondary data obtained from West Jakarta Health Office (2016-August 2019). The technique for catching rats involved the use of a trap or live trap (not kill-traps), while the identification of the rats and ectoparasites was made in the laboratory. It was found that more rats were caught in Cengkareng Timur Village, Cengkareng District, with a percentage of 14.8% while the least in Duri Kepa, Kapuk, Kedaung Kali Angke and Kedoya Utara with a percentage 3,7%. The rats were mostly found in East Cengkareng Sub-District, with the most common type being Rattus rattus (74.1 %) and the least is Suncus murinus (11,1%), and more male rats were caught (66.7%) and female 33,3%. The type of ectoparasite found in the rats was fleas. Xenopsylla cheopis was the most common type, at 83.3% and more fleas were male, at 66.7%. The most common rats species is Rattus rattus .The ectoparasite most commonly found in them was the female flea Xenopsylla cheopis. This study aimed to determine the presence and species of the rats and shrews that can potentially cause leptospirosis in West Jakarta and the species of ectoparasites found in them. Methods: The research was a descriptive study employing a cross-sectional approach. The study population was all species of rats and shrews in the region and the sample collection technique used was purposive sampling. The traps were installed in the homes of respondents who had suffered from leptospirosis and their closest neighbors ...